2021
DOI: 10.1093/bib/bbaa426
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics and system biology approach to identify the influences of COVID-19 on cardiovascular and hypertensive comorbidities

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infected individuals that have hypertension or cardiovascular comorbidities have an elevated risk of serious coronavirus disease 2019 (COVID-19) disease and high rates of mortality but how COVID-$19$ and cardiovascular diseases interact are unclear. We therefore sought to identify novel mechanisms of interaction by identifying genes with altered expression in SARS-CoV-$2$ infection that are relevant to the pathogenesis of cardiovascular disease and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 74 publications
1
28
0
1
Order By: Relevance
“…During SARS-CoV-2 infection, testosterone level may be elevated because ACE-2 is expressed by Leydig cell and can be hijacked by the virus (Nashiry et al, 2021), which in turn leads to inflammatory pyroptosis in Leydig cells and increased extracellular ATP levels (Zhang et al, 2017). These extracellular ATPs activate P2X receptors expressed in Leydig cells (Antonio et al, 2009) and promote testosterone secretion (Foresta et al, 1996).…”
Section: Sex Differences Regulate Atp-p2x7r-mediated Nlrp3 Inflammasome Activationmentioning
confidence: 99%
“…During SARS-CoV-2 infection, testosterone level may be elevated because ACE-2 is expressed by Leydig cell and can be hijacked by the virus (Nashiry et al, 2021), which in turn leads to inflammatory pyroptosis in Leydig cells and increased extracellular ATP levels (Zhang et al, 2017). These extracellular ATPs activate P2X receptors expressed in Leydig cells (Antonio et al, 2009) and promote testosterone secretion (Foresta et al, 1996).…”
Section: Sex Differences Regulate Atp-p2x7r-mediated Nlrp3 Inflammasome Activationmentioning
confidence: 99%
“…The first symptoms of COVID-19 resemble those of many other infections and inflammatory conditions that affect the respiratory system; they include fever, sneezing and rhinitis, persistent cough, and fatigue with body ache [2]. However, an infected patient can rapidly develop additional and more severe symptoms that can be life-threatening and require intensive care intervention; these include pneumonia, severe shortness of breath, diarrhea, dispersed thrombosis, and vascular inflammation [3,4]. An additional issue in caring for patients with COVID-19 is the presence of comorbidities that interact with COVID-19, particularly pulmonary and vascular conditions, which can greatly worsen the patient's prognosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…In SARS-CoV-2 patients, this might be functioning as a negative regulator of the T-cell activation so that there is a considerable balance between the activation and overactivation after infection. Recent studies show that the presence of GNLY can also be observed with COVID-19 patients having heart disease [ 31 ]. GNLY functions as a chemoattractant for T cells, monocytes and other inflammatory cells and stimulates several other cytokines and also helps in the recruitment of immune cells to the infection site as observed in SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…We have discovered several significant miRNAs in the interaction between Crohn’s and COVID-19 such as hsa-mir-1-3p, hsa-mir-124-3p, hsa-mir-129-2-3p. Studies have shown that miR-1-3p is known to be involved in heart diseases [ 31 ] and also plays significant roles in the development of human cancers such as lung cancer, bladder cancer or prostate cancer [ 77 ]. These two mi-RNAs are also available in the network of ulcerative colitis and COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation